Financial Uncertainty in Germany and its Impact on Western European Terrorism - Mario Jovanovic (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This paper analyses the link between the VDAX as a proxy for European financial uncertainty and the number of terror incidents in Western Europe. Considering data of the Global Terrorism Database, the number of terror incidents does - on average - not affect financial uncertainty. In contrast, based on a behavioral model of terrorism motivated by Schmid and de Graaf (1982), lagged financial uncertainty contains information for the risk of terror events. Estimation results of the negative binominal quasi maximum likelihood count data model confirm an inverse impact of lagged financial uncertainty on terrorism. Furthermore, empirical evidence leads to the conclusion of average lead time for terror incidents of 6 month. These results are potentially important for terror prevention. – – Dieses Papier untersucht den Zusammenhang zwischen dem VDAX als Proxy für europäische Finanzmarktunsicherheit und der Anzahl von Terroranschlägen in Westeuropa. Unter Berücksichtigung von Daten der Datenbank Global Terrorism Database kann gezeigt werden, dass - im Durchschnitt - Terrorismus keinen Effekt auf die Finanzmarktunsicherheit hat. Ausgehend von einem terroristischen Verhaltensmodell, welches von Schmid und de Graaf (1982) motiviert wird, kann gezeigt werden, dass verzögerte Finanzmarktunsicherheit Informationen für das Risiko von Terroranschlägen enthält. Schätzergebnisse eines effizienten Zähldatenmodells bestätigen einen reziproken Zusammenhang zwischen verzögerter Finanzmarktunsicherheit und Ausmaß des Terrorismus. Empirische Resultate implizieren darüber hinaus eine durchschnittlich sechsmonatige Vorbereitungszeit für einen Terroranschlag. Die Ergebnisse dieses Papiers sind möglicherweise relevant für die Prävention von Terroranschlägen.
Keywords: C25; G02; Z10; 330; VDAX; terror events; forecasting; count data; VDAX; terror events; forecasting; count data